Removal of Cresol Red by Adsorption Using Wastepaper - Salman, Mohamad; Demir, Muslum; Tang, Kuok Ho Daniel; Cao, Linh Thi Thuy; Bunrith, Seng; Chen, Tse-Wei; Darwish, Noura M.; AlMunqedhi, Bandar M.; Hadibarata, Tony (Industrial and Domestic Waste Management, 2022)
The utilization of less expensive and more effective adsorbents derived from a variety of basic materials has been investigated. The research aimed to investigate the feasibility of employing waste paper as the adsorbent to remove the cresol red (CR) dye from wastewater through adsorption mechanism. Langmuir, Jovanovic, and Freundlich model were observed for isotherms models, while pseudo-first-order and pseudo-second-order were examined for kinetic models. The results indicated that increasing the adsorbent dose and contact time gave no significant effect to adsorption capacity while adsorption capacity increased with the increasing of pH until it reached a maximum at pH 8, and raising the starting dye concentration leads in a significant increase in adsorption capacity (16.7 mg/g). When the experimental adsorption isotherms and kinetic were fitted using the Freundlich models and pseudo-second-order model, it was discovered that those models were more accurately represented by the data, as indicated by a high correlation coefficient (R2) of 0.974 and 0.963.